Identifying SARS-CoV-2 proteases - Müller, Christa E.; Gütschow, Michael (Henry Stewart Talks, 2021)
The two SARS-CoV-2 proteases found and their mechanisms of action, Designing inhibitors to these proteases, Steps taken in this research, Future work